Using data mining in the manufacturing systems for CAD model analysis and classification. (18th July 2008) - Al-Mubaid, Hisham; Abouel Nasr, Emad S.; Kamrani, Ali K.
The applications of data mining in engineering and manufacturing are enormous and useful for helping in the analysis of large data and information repositories for the discovery of trends, patterns and knowledge. In industrial engineering and manufacturing systems, the data may contain valuable information, or example, in downstream CAM applications such as Computer Aided Process Planning (CAPP). In this paper, we present a new approach for mining large quantities of machining features, Computer-Aided Design (CAD) models and manufacturing data. The approach is based on data mining and uses learning-logic classification techniques for mining 3D CAD data. The proposed approach was evaluated in CAD model analysis, specifically in classification tasks. The experimental results proved that the method is effective in terms of classification accuracy and can be used as an efficient data mining tool for CAD model analysis and classification.